Spontaneous pneumothorax in a young male athlete: A case report with review of literature - Maglica, Mirko; Jurčević, Ante; Jurčević, Branimira; Mišković, Josip (Indian Journal of Case Reports, 2024)
Spontaneous pneumothorax (SP) is a serious and life-threatening condition often caused by ruptured apical lung bulla in young male individuals. It is commonly associated with different syndromes but also occurs in healthy individuals. In this case report, we aim to discuss the etiology, clinical course, and surgical treatment of a 21-year-old male kickboxer with a right-sided pneumothorax that occurred during a sparring session. A chest tube with negative suction was inserted to resolve the pneumothorax. Because there was no visible resolution, video-assisted thoracoscopic surgery (VATS) was performed. During VATS, a large, apically placed, ruptured lung bulla, was revealed and removed. One month after surgery, the patient is in great clinical condition. There are no signs of a recurrence of SP.